Aids to management of headache disorders in primary care (2nd edition): on behalf of the European Headache Federation and Lifting The Burden: the Global Campaign against Headache - Steiner, T. J.; Jensen, R.; Katsarava, Z.; Linde, M.; MacGregor, E. A.; Osipova, V.; Paemeleire, K.; Olesen, J.; Peters, M.; Martelletti, P. (Journal of headache and pain, 2019)
The Aids to Management are a product of the Global Campaign against Headache, a worldwide programme of action conducted in official relations with the World Health Organization. Developed in partnership with the European Headache Federation, they update the first edition published 11 years ago. The common headache disorders (migraine, tension-type headache and medication-overuse headache) are major causes of ill health. They should be managed in primary care, firstly because their management is generally not difficult, and secondly because they are so common. These Aids to Management , with the European principles of management of headache disorders in primary care as the core of their content, combine educational materials with practical management aids. They are supplemented by translation protocols, to ensure that translations are unchanged in meaning from the English-language originals. The Aids to Management may be individually downloaded and, as is the case for all products of the Global Campaign against Headache, are available without restriction for non-commercial use.